Dye bonding to TiO2: in situ attenuated total reflection infrared spectroscopy study, simulations, and correlation with dye-sensitized solar cell characteristics - Völker, Barbara; Wölzl, Florian (Langmuir, 2012)
Processing dye-sensitized solar cells gains more and more importance as interest in industrial applications grows daily. For large-scale processing and optimizing manufacturing in terms of environmental acceptability as well as time and material saving, a detailed knowledge of certain process steps is crucial. In this paper we concentrate on the sensitizing step of production, i.e., the anchoring of the dye molecules onto the TiO2 semiconductor. A vacuum-tight attentuated total reflection infrared (ATR-IR) flow-through cell was developed, thus allowing measurements using a vacuum spectrometer to monitor infiltration of dye molecules into the porous TiO2 film in situ at high sensitivity. In particular, the influence of the anchor and backbone of perylene dye molecules as well as the influence of solvents on the adsorption process was investigated. The experiments clearly show that an anhydride group reacts much slower than an acid group. A significantly lower amount of anhydride dye can be adsorbed on the films. Ex situ transmission experiments furthermore indicate that the availability of OH groups on the TiO2 surface may limit dye adsorption. Also the backbone and base frame of the dye can influence the adsorption time drastically. Electrical cell characteristics correlate with the amount of adsorbed dye molecules determined by in situ ATR-IR measurements. The latter is also sensitive toward the diffusion of the dye through the porous layer. To gain a deeper understanding of the interplay between diffusion and adsorption, simulations were performed that allowed us to extract diffusion and adsorption constants. Again it was demonstrated that the anchoring group has a strong effect on the adsorption rate. The influence of the solvent was also studied, and it was found that both adsorption and desorption are affected by the solvent. Protic polar solvents are able to remove bound dye molecules, which is a possible pathway of cell degradation. Most importantly, the analysis shows the potential of this approach for the evaluation of molecules or additives concerning their characteristics important for cell processing.